Klinefelter's syndrome - Etem, Ebru Önalan; Elyas, Halit (My University, 2010)
Klinifelter sendromu (Klinefelter's syndrome; KS) is a primary hypogonadal disorder of genetic origin characterized by the existence of an X-chromosome polysomy in male patients. The main clinical characteristics in the adolescent or young adult are small firm testes, gynaecomastia, eunuchoid body proportions, azoospermia and high levels of gonadotrophins with normal/low levels of testosterone. Medical problems of KS include osteoporosis, otoimmun diseases, non-hodgkin lenfoma and male breast cancer. Treatments for KS include regular checkups, medications, and counseling. Cytogenetic analysis and genetic counseling would be helpful in KS males with azoospermia and oligospermia by assesing the genetic risks of the offsprigs provided by assisted reproductive techniques. The potential inheritance risk of this genetic disorder to offspring provides an information for screening infertile males prior to ICSI.
Kli?ni?felter sendromu
Keywords: gonadotropin; testosterone; autoimmune disease; azoospermia; breast cancer; chromosome analysis; cytogenetics; genetic association; genetic counseling; gonadotropin blood level; gynecomastia; Hodgkin disease; human; hypogonadism; infertility; infertility therapy; intellectual impairment; karyotype 47,XXY; Klinefelter syndrome; male breast; nonhodgkin lymphoma; oligospermia; osteoporosis; pathophysiology; phenotype; progeny; review; X chromosome